Negative pressure wound therapy using polyvinyl alcohol foam to bolster full‐thickness mesh skin grafts in dogs. Issue 3 (2nd February 2017) - Or, Matan; Van Goethem, Bart; Kitshoff, Adriaan; Koenraadt, Annika; Schwarzkopf, Ilona; Bosmans, Tim; de Rooster, Hilde
Abstract: Objective: To report the use of negative pressure wound therapy (NPWT) with polyvinyl alcohol (PVA) foam to bolster full‐thickness mesh skin grafts in dogs. Study Design: Retrospective case series. Animals: Client‐owned dogs (n = 8). Material and Methods: Full‐thickness mesh skin graft was directly covered with PVA foam. NPWT was maintained for 5 days (in 1 or 2 cycles). Grafts were evaluated on days 2, 5, 10, 15, and 30 for graft appearance and graft take, granulation tissue formation, and complications. Results: Firm attachment of the graft to the recipient bed was accomplished in 7 dogs with granulation tissue quickly filling the mesh holes, and graft take considered excellent. One dog had bandage complications after cessation of the NPWT, causing partial graft loss. The PVA foam did not adhere to the graft or damage the surrounding skin. Conclusion: The application of NPWT with a PVA foam after full‐thickness mesh skin grafting in dogs provides an effective method for securing skin grafts, with good graft acceptance. PVA foam can be used as a primary dressing for skin grafts, obviating the need for other interposing materials to protect the graft and the surrounding skin.